Reflecting on the past, present, and future of social security systems in Africa with specific reference to selected countries (The Strategic Review for Southern Africa, 2021)
The concept of social security is not a new phenomenon to sub-Saharan Africa. Before the introduction of formal social security systems, local communities had their own unique traditional ways of protecting their members from the hazards and vicissitude of life. This paper provides an overview of social security in sub-Saharan Africa. Arguably, high unemployment in the region has contributed towards the rise of the informal sector. Nevertheless, this sector has been precluded from the existing formal social security arrangements. Through an extensive and systematic review of literature on social security, it was established that existing formal social security systems in sub-Saharan Africa are fragmented and lack inclusivity. The findings revealed that the majority of the population is excluded from formal social security schemes because they work in the informal sector. However, the existing formal social security schemes are generally labour-centred and state-regulated. The recommendations include the transformation of existing social security measures to include the informal sector and other vulnerable groups. In light of the low coverage, the social security narrative needs to be revisited. There is a need to integrate and synchronise existing formal social security strategies with traditional social security arrangements in the region.